Association between polymorphisms in interleukin-17A and interleukin-17F genes in colorectal, breast and nasopharyngeal cancers at a tertiary hospital in Kuala Lumpur, Malaysia - Samiei, Golnaz (2014)
Interleukin-17 (IL-17) is a CD4+ T cell-drived proinflammatory cytokines. IL-17 plays a pivotal role in tissue inflammation by inducing the expression of proinflammatory and neutrophil-mobilizing cytokines. IL-17 also has a critical role in inflammation and cancer. Polymorphisms of IL-17A and IL-17F has been expected to be associated with disease. The purpose of this study was to demonstrate whether there was an association between two polymorphisms of IL-17A/rs2275913 (G-197A) and IL-17F/rs763780 (A7488G) genes and risk of sporadic colorectal, breast and nasopharyngeal cancers. One single-nucleotide polymorphism (SNP) in IL-17A/rs2275913 (G197A) and another SNP in IL-17F/rs763780 (A7488G) were determined by using genotype-specific polymerase chain reaction-(PCR) and restriction fragment length polymorphism (RFLP). DNA Sequencing was conducted to confirm the RFLP results in colorectal, breast and nasopharyngeal cancer patients and apparently healthy individuals. PCRRFLP was carried out on isolated DNA from blood samples from sixty-three breast, seventy-two nasopharyngeal cancer patients, eighty apparently healthy individuals, and forty-seven colorectal cancer paraffin-embedded blocks to identify the association between IL-17A/rs2275913 (G197A) and IL-17F/rs763780 (A7488G) polymorphisms and risk of colorectal, breast, and nasopharyngeal cancers in Malaysia. This is the first report on the IL-17 gene polymorphisms in cancer patients in Malaysia. We compared the alleles and genotypes frequencies of IL-17A/rs2275913 (G197A) and IL-17F/rs763780 (A7488G) in patients with colorectal, breast, and nasopharyngeal. Statistical analysis of the results indicated that the homozygous AA genotype and the A allele of IL-17A/rs2275913 G197A were more frequent in colorectal cancer patients. Therefore, our study determined that IL-17A, but not IL-17F, contributes to colorectal cancer susceptibility. The positive association was found between IL-17F/rs763780 (A7488G) genotype in colorectal cancer with histological grade (P value< 0.005). No significant relationship was found between IL-17A/rs2275913 (G197A) and IL- 17F/rs763780 (A7488G) with breast and nasopharyngeal cancer. The results of this study emphasized the significance of IL-17A/rs2275913 (G197A) gene polymorphism as the predisposing genetic parameters that confers the genetic susceptibility for colorectal cancer in Malaysia. It demands expanding the cases and further investigations to confirm the effect of IL-17A/rs2275913 (G197A) polymorphism.